Of Worlds and Artworks : A Relational View on Artistic Practices from Africa and the Diaspora (Africa Multiple, 2024)
The edited volume Of Worlds and Artworks: A Relational View on Artistic Practices from Africa and the Diaspora, part of the Africa Multiple series (Volume 3), offers an interdisciplinary exploration of artistic creation across a spectrum of media, including literature, visual arts, film, and performance. Edited by Ute Fendler, Marie-Anne Kohl, Gilbert Shang Ndi, Christopher Joseph Odhiambo, and Clarissa Vierke, the book investigates how artistic practices engage in “worlding” processes. It emphasises the movement, interaction, and creation of relations that transcend geographic boundaries. The main objective of this book is to challenge the conventional fixed perceptions often associated with area studies, particularly those related to Africa, and instead present it as a flexible and interconnected space influenced by various global interactions. This relational approach not only establishes connections within Africa but also with other regions such as the Indian Ocean, the Atlantic, and Europe.
Keywords: World; Relationality; artworks; Africa; Diaspora